Battery diaphragm, secondary battery and electric equipment
By setting an inorganic heat-resistant layer on the surface of the battery separator base and embedded polymer particles to form a raised structure, the problem of insufficient thermal stability of the battery separator is solved, the cycle performance and safety performance of the battery are improved, and the production cost is reduced.
Patent Information
- Application Number
- CN202411364384.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-27
- Publication Date
- 2024-12-17
AI Technical Summary
The existing battery separators have poor thermal stability, high production costs and pose risks to battery consistency, long-term reliability and safety performance.
An inorganic heat-resistant layer is provided on the surface of the battery separator substrate, and polymer particles are embedded in the inorganic heat-resistant layer to form a raised structure, and the distribution density of the raised structure is adjusted to enhance the hot press bonding performance and the electrolyte infiltration performance.
It significantly improves the cycle performance and safety performance of the battery, reduces production costs, and enhances the hot pressing bonding performance of the battery separator and the electrode sheet.
Smart Images

Figure CN119153889A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of batteries, and in particular relates to a battery separator, a secondary battery and an electrical device. Background Art
[0002] New energy batteries, mainly lithium batteries, are mainly composed of five parts: positive electrode materials, negative electrode materials, diaphragms, electrolytes and packaging materials. Among them, the diaphragm located between the positive electrode materials and the negative electrode materials has the functions of preventing direct contact between the positive and negative electrodes, preventing battery short circuits, and transmitting ions. It is a key component that affects the battery cycle performance and safety performance. At present, the commercial battery diaphragms are mainly polyolefin diaphragms based on polyethylene, polypropylene, etc. Although such diaphragms have good insulation, mechanical strength and electrochemical stability, their thermal stability is poor. In order to improve the thermal stability of polyolefin diaphragms, inorganic materials such as ceramics are generally coated on the surface of polyolefin diaphragms to form a coated diaphragm with an inorganic heat-resistant layer. Conventional batch-used coated diaphragms are mostly coated twice or three times. For example, a pure ceramic coating is first coated on the surface of the polyolefin diaphragm by micro-gravure roller coating, and then a bonding layer is coated on the surface of the pure ceramic coating by spraying, spot coating, dip coating or roller coating, and finally a coated diaphragm is formed; however, the production cost of the coated diaphragm is high, and it has great risks to battery consistency, long-term reliability and safety performance. Summary of the invention
[0003] The object of the present invention is to overcome the deficiencies of the prior art and provide a battery separator, a secondary battery and an electrical device.
[0004] To achieve the above object, the technical solution adopted by the present invention is:
[0005] In a first aspect, the present invention provides a battery separator, comprising a separator substrate and a coating disposed on at least one side of the separator substrate; the coating comprises an inorganic heat-resistant layer containing inorganic particles and polymer particles;
[0006] The inorganic heat-resistant layer has a first surface and a second surface that are arranged opposite to each other, and the first surface of the inorganic heat-resistant layer is in contact with the diaphragm substrate; at least part of the polymer particles are embedded in the inorganic heat-resistant layer, and a convex structure is formed on the second surface of the inorganic heat-resistant layer; the distribution density of the convex structure is 500 to 3700 / mm 2 .
[0007] As an embodiment of the present invention, the mass proportion of the polymer particles in the coating is 2% to 23%.
[0008] As an embodiment of the present invention, the glass transition temperature of the polymer particles is 10°C to 100°C.
[0009] As an embodiment of the present invention, the polymer particles include at least one of butyl methacrylate-acrylonitrile-styrene copolymer, butyl methacrylate-acrylamide-styrene copolymer, butyl methacrylate-acrylic acid-styrene copolymer, butyl methacrylate-ethylene oxide-styrene copolymer, butyl methacrylate-hexafluoropropylene-styrene copolymer, butyl methacrylate-acetate-styrene copolymer, and vinylidene fluoride-hexafluoropropylene-acrylate copolymer.
[0010] As an embodiment of the present invention, the particle size Dv50 of the inorganic particles is 0.1 to 1.5 μm; and / or the particle size Dv50 of the polymer particles is 2 to 9 μm.
[0011] As an embodiment of the present invention, the inorganic heat-resistant layer further comprises a first adhesive and a second adhesive;
[0012] The first adhesive includes at least one of polyacrylate, polyacrylic acid, polyacrylamide, and silicon phosphorus sol;
[0013] The second adhesive includes at least one of polyacrylate, sodium carboxymethyl cellulose, polyacrylic acid, polyacrylonitrile, polyacrylic acid copolymer, and silicon-phosphorus sol.
[0014] As an embodiment of the present invention, the mass proportion of the first adhesive in the coating is 1% to 10%; and / or the mass proportion of the second adhesive in the coating is 0.01% to 2%.
[0015] As an embodiment of the present invention, at least one of the conditions (1) to (5) is satisfied:
[0016] (1) The average height of the protrusion structure is 2.8 to 30 μm;
[0017] (2) There are gaps between the inorganic particles, and at least part of the polymer particles are embedded in the gaps;
[0018] (3) The polymer particles are solid particles;
[0019] (4) The inorganic particles include at least one of alumina, boehmite, silicon dioxide, magnesium hydroxide, and barium sulfate;
[0020] (5) The air permeability of the battery separator is 160 to 400 s / 100 cc.
[0021] In a second aspect, the present invention provides a secondary battery, comprising a positive electrode sheet, a negative electrode sheet and the above-mentioned battery separator; the average gap between the above-mentioned battery separator and the positive electrode sheet and the negative electrode sheet is 0 to 9 μm.
[0022] In a third aspect, the present invention provides an electrical device, comprising the above-mentioned secondary battery, wherein the secondary battery serves as a power supply for the electrical device.
[0023] Compared with the prior art, the present invention has the following beneficial effects:
[0024] The battery separator of the present invention is provided with an inorganic heat-resistant layer on the surface of the separator substrate to enhance thermal stability, and at the same time, polymer particles are embedded in the inorganic heat-resistant layer to form a protrusion structure, and the hot pressing bonding performance between the battery separator and the pole piece is enhanced by adjusting the distribution density of the protrusion structure, and at the same time, the wetting performance of the electrolyte is improved, thereby significantly improving the cycle performance and safety performance of the battery. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 This is a schematic diagram of the structure of the battery separator obtained in Example 1;
[0026] Figure 2 This is a schematic diagram of the structure of the battery separator obtained in Example 18;
[0027] Figure 3 This is a surface SEM image of the coating side of the battery separator obtained in Example 2;
[0028] Figure 4 This is a cross-sectional SEM image of the battery separator obtained in Example 2 before hot pressing;
[0029] Figure 5 This is a cross-sectional SEM image of the battery separator obtained in Example 2 after hot pressing. DETAILED DESCRIPTION
[0030] In order to better illustrate the purpose, technical solutions and advantages of the present invention, the present invention will be further described below in conjunction with specific embodiments and comparative examples, the purpose of which is to understand the content of the present invention in detail, rather than to limit the present invention. All other embodiments obtained by those of ordinary skill in the art without making creative work premise belong to the protection scope of the present invention. The experimental reagents and instruments involved in the implementation of the present invention, unless otherwise specified, are all commonly used common reagents and instruments.
[0031] According to a first aspect of the present invention, there is provided a battery separator, comprising a separator substrate and a coating provided on at least one side of the separator substrate; the coating comprises an inorganic heat-resistant layer containing inorganic particles and polymer particles;
[0032] The inorganic heat-resistant layer has a first surface and a second surface that are arranged opposite to each other, and the first surface of the inorganic heat-resistant layer is in contact with the diaphragm substrate; at least part of the polymer particles are embedded in the inorganic heat-resistant layer, and a convex structure is formed on the second surface of the inorganic heat-resistant layer; the distribution density of the convex structure is 500 to 3700 / mm2 .
[0033] The battery separator of the present invention is provided with an inorganic heat-resistant layer on the surface of the separator substrate to enhance thermal stability, and at the same time, polymer particles are embedded in the inorganic heat-resistant layer to form a protrusion structure, and the hot pressing bonding performance of the battery separator is controlled by adjusting the distribution density of the protrusion structure, so that a certain space is formed between the battery separator and the electrode to accommodate the electrolyte, thereby improving the wetting performance of the electrolyte and enhancing the cycle performance of the battery.
[0034] Optionally, the distribution density of the protrusion structure can be 500 / mm 2 , 1000 pieces / mm 2 , 1500 pieces / mm 2 , 2000pcs / mm 2 , 2500pcs / mm 2 , 3000 pieces / mm 2 , 3200 pieces / mm 2 , 3700 pieces / mm 2 The range value of one or both of them.
[0035] In addition, the separator matrix in the above-mentioned battery separator can be selected from at least one of polyolefin separators (such as polyethylene separators, polypropylene separators), PET non-woven fabrics, and polyimide porous films.
[0036] Preferably, the inorganic heat-resistant layer includes inorganic particles, and the particle size Dv50 ratio of the inorganic particles to the polymer particles is (0.1-1.5):(2-9). Optionally, the particle size Dv50 ratio of the inorganic particles to the polymer particles can be specifically 0.1:9, 0.3:8, 0.5:7, 0.7:6, 0.9:5, 1.1:4, 1.3:3, 1.5:2 or any two of the range values.
[0037] By regulating the ratio of the particle size Dv50 of inorganic particles to that of polymer particles, the heat resistance and adhesion performance of the battery separator can be balanced. When the particle size Dv50 ratio of inorganic particles to polymer particles is within the above range, the battery separator can have both good heat resistance and excellent adhesion performance, thereby better improving the battery cycle performance.
[0038] As an embodiment of the present invention, the mass proportion of the polymer particles in the coating is 2% to 20%. Optionally, the mass proportion of the polymer particles in the coating can be 2%, 3%, 5%, 7%, 9%, 11%, 13%, 15%, 17%, 19%, 20% or any two of the range values.
[0039] The mass proportion of polymer particles in the coating will affect the heat resistance, direct current resistance (DCR) and hot pressing bonding performance of the battery separator. When the mass proportion of polymer particles in the coating is within the above range, it can not only enable the battery separator to maintain high heat resistance, low direct current resistance and better dynamic performance, but also better enhance the hot pressing bonding effect between the battery separator and the electrode, and improve the processing and manufacturing performance of the battery separator.
[0040] As an embodiment of the present invention, the glass transition temperature of the polymer particles is 10° C. to 100° C. Optionally, the glass transition temperature of the polymer particles can be specifically a range of one or any two of 10° C., 20° C., 30° C., 40° C., 50° C., 60° C., 70° C., 80° C., 90° C., and 100° C.
[0041] The glass transition temperature of polymer particles mainly affects the hot pressing bonding performance of battery separators. When the glass transition temperature is 10°C to 100°C, the battery separator can have better hot pressing bonding performance. The glass transition temperature (Tg) of polymer particles can be measured by direct scanning calorimetry (DSC), and the specific reference can be made to the standard GB / T19466.
[0042] As an embodiment of the present invention, the polymer particles include at least one of butyl methacrylate-acrylonitrile-styrene copolymer, butyl methacrylate-acrylamide-styrene copolymer, butyl methacrylate-acrylic acid-styrene copolymer, butyl methacrylate-ethylene oxide-styrene copolymer, butyl methacrylate-hexafluoropropylene-styrene copolymer, butyl methacrylate-acetate-styrene copolymer, and vinylidene fluoride-hexafluoropropylene-acrylate copolymer. When the polymer particles are selected from the above polymers, not only can the battery separator have better hot pressing bonding performance, but also it is beneficial to improve the electrochemical performance of the assembled battery.
[0043] As an embodiment of the present invention, the particle size Dv50 of the inorganic particles is 0.1-1.5 μm; and / or, the particle size Dv50 of the polymer particles is 2-9 μm. Optionally, the particle size Dv50 of the inorganic particles can be specifically 0.1 μm, 0.2 μm, 0.4 μm, 0.6 μm, 0.8 μm, 1.0 μm, 1.2 μm, 1.4 μm, 1.5 μm, or any two of the range values; the particle size Dv50 of the polymer particles can be specifically 2 μm, 2.5 μm, 3 μm, 3.5 μm, 4 μm, 4.5 μm, 5 μm, 5.5 μm, 6 μm, 6.5 μm, 7 μm, 7.5 μm, 8 μm, 8.5 μm, 9 μm, or any two of the range values.
[0044] The combination of inorganic particles and polymer particles with the above-mentioned particle size Dv50 can make the battery separator have better heat resistance, hot pressing bonding performance and dynamic performance, and can also effectively reduce the risks of powder loss and tab misalignment. The particle size Dv50 of inorganic particles or polymer particles can be measured by Malvern 3000 laser particle size analyzer.
[0045] As an embodiment of the present invention, the inorganic heat-resistant layer further comprises a first adhesive and a second adhesive;
[0046] The first adhesive includes at least one of polyacrylate, polyacrylic acid, polyacrylamide, and silicon phosphorus sol;
[0047] The second adhesive includes at least one of polyacrylate, sodium carboxymethyl cellulose, polyacrylic acid, polyacrylonitrile, polyacrylic acid copolymer, and silicon-phosphorus sol.
[0048] The first adhesive mainly plays a bonding role in the coating to ensure the formation of a stable solidified interface between the inorganic particles and between the inorganic particles and the surface of the diaphragm matrix, thereby improving the heat resistance stability of the battery diaphragm; its mass proportion in the coating can be 1% to 10%, preferably 2% to 6%, specifically 1%, 2%, 3%, 4%, 5%, 7%, 8%, 9%, 10% or any two of the range values.
[0049] The second adhesive mainly plays a dispersing and bonding role in the coating, and its mass proportion in the coating can be 0.01% to 2%, preferably 0.5% to 1.5%, specifically 0.01%, 0.1%, 0.2%, 0.3%, 0.4%, 0.6%, 0.8%, 1%, 1.2%, 1.4%, 1.6%, 1.8%, 2% or any two of the range values.
[0050] When the mass proportion of the first adhesive in the coating is 1% to 10%, or the mass proportion of the second adhesive in the coating is 0.01% to 2%, it is beneficial to better improve the heat resistance, uniformity and electrolyte infiltration performance of the battery separator.
[0051] As an embodiment of the present invention, the average height of the protrusion structure is 2.8-30 μm. When the average height of the protrusion structure is 2.8-30 μm, the battery separator and the pole piece can maintain good bonding performance while having better dynamic performance.
[0052] As an embodiment of the present invention, there are gaps between the inorganic particles in the inorganic heat-resistant layer, and at least part of the polymer particles are embedded in the gaps. Furthermore, the polymer particles are solid particles. When the polymer particles are embedded in the gaps between the inorganic particles, more infiltration channels can be provided for the electrolyte in the battery during the cycle process, and more buffer space can be provided for the expansion of the pole piece during the cycle process, thereby improving the long-term performance of the battery.
[0053] As an embodiment of the present invention, the inorganic particles include at least one of aluminum oxide, boehmite (γ-AlOOH), silicon dioxide, magnesium hydroxide, and barium sulfate. Preferably, the inorganic particles are a mixture of boehmite and barium sulfate; the inorganic particles are composed of boehmite and barium sulfate, which can ensure that the surface density of the battery separator is reduced while taking into account better heat resistance. Further, in order to optimize the heat resistance of the battery separator, the mass ratio of boehmite to barium sulfate in the inorganic particles is 1: (0.1-0.5).
[0054] As an embodiment of the present invention, the air permeability of the battery separator is 160-400s / 100cc; optionally, the air permeability of the battery separator can be specifically 160s / 100cc, 200s / 100cc, 250s / 100cc, 300s / 100cc, 350s / 100cc, 400s / 100cc, or any two of them. Studies have found that battery separators in the above air permeability range can have both lower impedance and better dynamic performance.
[0055] The air permeability of the above battery separator can be measured by the following test method: take an area of 10mm 2 The isolation film sample is placed in a Gurley air permeability tester and the time required for 100cc volume of gas to pass through is counted.
[0056] In a second aspect, the present invention provides a secondary battery, comprising a positive electrode sheet, a negative electrode sheet and the above-mentioned battery separator; the average gap between the battery separator and the positive electrode sheet and the negative electrode sheet is 0 to 9 μm. By adjusting the average gap between the separator and the electrode sheet to be less than or equal to 9 μm, more infiltration channels can be provided for the electrolyte, and a buffer gap can be provided for the expansion of the electrode sheet during the cycle, thereby better improving the long-term performance of the battery.
[0057] The secondary battery includes at least one of a wound soft-pack battery, a wound aluminum shell battery, a wound cylindrical battery, a laminated soft-pack battery, a laminated aluminum shell battery, etc.; the pole pieces in the secondary battery include positive pole pieces and negative pole pieces, and the positive electrode active material in the positive pole piece may include at least one of a nickel-cobalt-manganese ternary material, a lithium iron phosphate material, and a lithium iron manganese phosphate material; the negative electrode active material in the negative pole piece includes at least one of a carbon-based material, a silicon-based material, and a tin-based material.
[0058] In a third aspect, the present invention provides an electrical device, comprising the above-mentioned secondary battery, wherein the secondary battery serves as a power supply for the electrical device.
[0059] In order to clearly understand the technical solution of the present invention, the present invention is further described in detail below in conjunction with specific embodiments. These embodiments should not be construed as limiting the scope of protection claimed by the present invention.
[0060] Example 1
[0061] This embodiment provides a battery separator (such as Figure 1 The preparation method thereof comprises the following steps:
[0062] S1, inorganic particles (α-Al2O3, particle size Dv50 is 0.5 μm), a first adhesive (polyacrylate), a second adhesive (sodium hydroxymethyl cellulose) and polymer particles (butyl methacrylate-acrylonitrile-styrene copolymer, particle size Dv50 is 5.1 μm) are mixed in a mass ratio of 90.0:4.9:1.0:4.0, and a wetting agent is added and stirred to mix evenly to obtain a coating slurry;
[0063] S2. Use micro-gravure process to apply the coating slurry in S1 to one side of the diaphragm substrate (PE diaphragm with a thickness of 7 μm) with a coating thickness of 2 μm, then dry at 60°C, roll up, and cut for later use.
[0064] Example 2
[0065] This embodiment provides a battery separator, which is different from Embodiment 1 in that the mass ratio of the inorganic particles, the first adhesive, the second adhesive and the polymer particles in step S1 is 87.7:5.1:1.1:6.0.
[0066] Example 3
[0067] This embodiment provides a battery separator, which is different from Embodiment 1 in that the mass ratio of the inorganic particles, the first adhesive, the second adhesive and the polymer particles in step S1 is 85.5:3.1:1.1:8.1.
[0068] Example 4
[0069] This embodiment provides a battery separator, which is different from Embodiment 1 in that the mass ratio of the inorganic particles, the first adhesive, the second adhesive and the polymer particles in step S1 is 80.9:5.1:1.2:12.1.
[0070] Example 5
[0071] This embodiment provides a battery separator, which is different from Embodiment 1 in that the mass ratio of the inorganic particles, the first adhesive, the second adhesive and the polymer particles in step S1 is 76.4:6.2:1.3:16.1.
[0072] Example 6
[0073] This embodiment provides a battery separator, which is different from Embodiment 1 in that the mass ratio of the inorganic particles, the first adhesive, the second adhesive and the polymer particles in step S1 is 71.8:6.6:1.4:20.2.
[0074] Example 7
[0075] This embodiment provides a battery separator, which is different from Embodiment 1 in that the mass ratio of the inorganic particles, the first adhesive, the second adhesive and the polymer particles in step S1 is 69.5:6.8:1.4:22.2.
[0076] Example 8
[0077] This embodiment provides a battery separator, which is different from Embodiment 1 in that the mass ratio of the inorganic particles, the first adhesive, the second adhesive and the polymer particles in step S1 is 92.3:4.7:1.0:2.0.
[0078] Example 9
[0079] This embodiment provides a battery separator, which is different from Embodiment 1 in that the mass ratio of the inorganic particles, the first adhesive, the second adhesive and the polymer particles in step S1 is 83.99:10:0.01:6.
[0080] Example 10
[0081] This embodiment provides a battery separator, which is different from Embodiment 1 in that the mass ratio of the inorganic particles, the first adhesive, the second adhesive and the polymer particles in step S1 is 91:1:2:6.
[0082] Embodiment 11
[0083] This embodiment provides a battery separator, which is different from Embodiment 2 in that the particle size Dv50 of the inorganic particles in step S1 is 0.1 μm, and the particle size Dv50 of the polymer particles is 9 μm.
[0084] Example 12
[0085] This embodiment provides a battery separator, which is different from Embodiment 2 in that the particle size Dv50 of the inorganic particles in step S1 is 1.5 μm, and the particle size Dv50 of the polymer particles is 2 μm.
[0086] Embodiment 13
[0087] This embodiment provides a battery separator, which is different from Embodiment 2 in that the material of the polymer particles in step S1 is butyl methacrylate-acrylamide-styrene copolymer.
[0088] Embodiment 14
[0089] This embodiment provides a battery separator, which is different from Embodiment 2 in that the material of the polymer particles in step S1 is butyl methacrylate-acrylic acid-styrene copolymer.
[0090] Embodiment 15
[0091] This embodiment provides a battery separator, which is different from Embodiment 2 in that the material of the polymer particles in step S1 is butyl methacrylate-ethylene oxide-styrene copolymer.
[0092] Example 16
[0093] This embodiment provides a battery separator, which is different from Embodiment 2 in that the material of the polymer particles in step S1 is butyl methacrylate-hexafluoropropylene-styrene copolymer.
[0094] Embodiment 17
[0095] This embodiment provides a battery separator, which is different from Embodiment 2 in that the material of the polymer particles in step S1 is vinylidene fluoride-hexafluoropropylene-acrylate copolymer.
[0096] Embodiment 18
[0097] This embodiment provides a battery separator, which is different from the embodiment 2 in that in step S2, the coating slurry in S1 is applied to both sides of the separator substrate. The structural schematic diagram of the obtained battery separator is as follows: Figure 2 shown.
[0098] Embodiment 19
[0099] This embodiment provides a battery separator, which is different from Embodiment 2 in that the inorganic particles in step S1 of the preparation method are boehmite and barium sulfate in a mass ratio of 1:0.3, the first adhesive is polyacrylamide, and the second adhesive is polyacrylic acid.
[0100] Comparative Example 1
[0101] This comparative example provides a battery separator, which is different from Example 2 in that the mass ratio of the inorganic particles, the first adhesive, the second adhesive and the polymer particles in step S1 is 92.4:5.4:1.2:1.
[0102] Comparative Example 2
[0103] This comparative example provides a battery separator, which is different from Example 1 in that the mass ratio of the inorganic particles, the first adhesive, the second adhesive and the polymer particles in step S1 is 60:6.8:1.4:31.8.
[0104] Table 1 Components in the coating of the battery separator in each embodiment and comparative example
[0105]
[0106]
[0107] Performance Testing
[0108] 1. The battery separators in each embodiment and comparative example were subjected to performance tests. The test results are shown in Table 2. The specific test methods are as follows:
[0109] 1) Test method for battery separator thickness: Take 2-3m battery separator and place it under the probe of Mahr thickness gauge for testing, and record the thickness data displayed by the equipment.
[0110] 2) Test method for battery separator air permeability: take area > 10mm 2 The battery separator sample is placed in a Gurley air permeability tester and the time required for 100cc of gas to pass through is counted.
[0111] 3) Test method for the distribution density of protrusion structures: Place the battery separator sample on the SEM sample stage, randomly select 10 positions, take a picture at a magnification of 500 times at each position, and count the protrusions within the field of view (170×227μm 2 ) is calculated, and then the average number of protrusion structures is calculated, that is, the distribution density of the protrusion structures in the battery separator is obtained.
[0112] 4) Test method for the average height of the raised structure: Use a Marr thickness gauge to stack 5 layers of battery diaphragms and place them flat on the test bench to test the battery diaphragm thickness H1, diaphragm matrix thickness H2 and inorganic heat-resistant layer thickness H3. The average height of the raised structure H0 = H1-H2-H3.
[0113] Table 2 Performance of battery separators in various embodiments and comparative examples
[0114]
[0115]
[0116] 2. The battery separators in the embodiments and comparative examples are stacked in order with the positive electrode sheets and the negative electrode sheets so that the battery separator is between the positive and negative electrode sheets, and the inner core is formed by winding, hot pressing and shaping (temperature is 95°C, pressure is 3MPa, time is 30s), and the tabs are welded to obtain a bare battery cell, and the bare battery cell is placed in an outer packaging aluminum-plastic film, and baked in an oven at 85±10°C for 24h, and the electrolyte is injected into the dried battery, and the battery is allowed to stand, formed, and divided to complete the preparation of a lithium-ion soft-pack battery;
[0117] The preparation of the positive electrode sheet comprises the following steps:
[0118] Lithium iron phosphate, polyvinylidene fluoride (PVDF), carbon black and polyvinyl pyrrolidone dry powder are mixed in a weight ratio of 97.55:1.8:0.5:0.15, and then added into N-methylpyrrolidone (NMP) and stirred thoroughly to form a positive electrode slurry with a solid content of 65% and a viscosity of 6000-9000 mPa·s, and then the positive electrode slurry is coated on a carbon-coated aluminum foil, dried, rolled and cut to obtain a positive electrode sheet;
[0119] The preparation of the above-mentioned negative electrode sheet includes the following steps:
[0120] Graphite, carbon black, sodium carboxymethyl cellulose, polyacrylonitrile and styrene acrylate powders are mixed in a weight ratio of 97:0.3:0.6:1.0:1.1, added into deionized water and stirred thoroughly to form a negative electrode slurry with a solid content of 48.5% and a viscosity of 2000-8000 mPa·s, and then the negative electrode slurry is coated on a copper foil, dried, rolled and cut to obtain a negative electrode sheet;
[0121] The electrolyte is a 1 mol / L lithium hexafluorophosphate solution, wherein the solvent is composed of DMC:EMC:EC in a volume ratio of 5:2:3 and contains 5% fluoroethylene carbonate (FEC).
[0122] The above-mentioned lithium-ion soft-pack battery was subjected to performance testing. The test results are shown in Table 3. The specific test method is as follows:
[0123] 1) Average gap between the battery separator coating and the electrode in the inner core (average gap at the R angle of the winding core): Average gap = [total thickness of the winding core - (total thickness of the positive electrode sheet + total thickness of the negative electrode sheet + total thickness of the separator)] / (number of winding layers - 1).
[0124] 2) Battery DCR test method: The battery is adjusted to 50% SOC state in a 25°C constant temperature box, and then the DC impedance value of the battery corresponding to 5C DC discharge for 10s is tested.
[0125] 3) Battery cycle performance test method: The lithium-ion soft-pack battery is cycled at 1C / 1C in a 25°C constant temperature box in the range of 0-100% SOC until the capacity retention rate of 2500 cycles is recorded, and the voltage range is 2.5V-3.65V. Capacity retention rate (%) = discharge specific capacity of the 2500th cycle / discharge specific capacity of the first cycle * 100%.
[0126] Table 3 Performance of lithium-ion soft-pack batteries corresponding to battery separators in various embodiments and comparative examples
[0127]
[0128]
[0129] According to the data in Table 3, the battery DCR of the lithium-ion soft-pack batteries in Examples 1 to 19 is ≤0.70 mΩ, and the capacity retention rate after 2500 cycles is more than 75%, indicating that the battery separator of the present invention has a low DC impedance value and can give the battery excellent long-term cycle performance. According to Comparative Example 2, if the distribution density of the protrusion structure is greater than 3700 / mm 2 , the battery DCR increases and the cycle performance decreases. This may be because when the distribution density is too large, the proportion of inorganic particles in the diaphragm decreases, causing the stability of the battery diaphragm to decrease.
[0130] In addition, the surface of the battery separator in Example 2 and its cross-section before and after hot pressing were observed for morphology. Figures 3 to 5 As shown, Figure 3 is the surface map of the battery separator, Figure 4 This is a cross-sectional view of the battery separator before hot pressing. Figure 5 This is a cross-sectional view of the battery separator after hot pressing. Figure 3 and Figure 4 It can be seen that the protrusion structure in the battery separator is composed of spherical or quasi-spherical polymer particles of different sizes embedded in the inorganic heat-resistant layer; at the same time, according to Figure 5 It can be found that the protruding structure in the battery separator and the active material layer in the pole piece are bonded under the action of heat pressing, and a certain electrolyte accommodation space is formed between the battery separator and the pole piece.
[0131] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.
Claims
1. A battery separator, characterized in that: It comprises a diaphragm substrate and a coating provided on at least one side of the diaphragm substrate; the coating comprises an inorganic heat-resistant layer containing inorganic particles and polymer particles; The inorganic heat-resistant layer has a first surface and a second surface that are arranged opposite to each other, and the first surface of the inorganic heat-resistant layer is in contact with the diaphragm substrate; at least part of the polymer particles are embedded in the inorganic heat-resistant layer, and a convex structure is formed on the second surface of the inorganic heat-resistant layer; the distribution density of the convex structure is 500 to 3700 / mm 2 .
2. The battery separator according to claim 1, characterized in that The mass proportion of the polymer particles in the coating is 2% to 23%.
3. The battery separator according to claim 1, characterized in that The glass transition temperature of the polymer particles is 10°C to 100°C.
4. The battery separator according to claim 1, characterized in that The polymer particles include at least one of butyl methacrylate-acrylonitrile-styrene copolymer, butyl methacrylate-acrylamide-styrene copolymer, butyl methacrylate-acrylic acid-styrene copolymer, butyl methacrylate-ethylene oxide-styrene copolymer, butyl methacrylate-hexafluoropropylene-styrene copolymer, butyl methacrylate-acetate-styrene copolymer, and vinylidene fluoride-hexafluoropropylene-acrylate copolymer.
5. The battery separator according to claim 1, characterized in that The particle size Dv50 of the inorganic particles is 0.1 to 1.5 μm; and / or the particle size Dv50 of the polymer particles is 2 to 9 μm.
6. The battery separator according to claim 1, characterized in that The inorganic heat-resistant layer further comprises a first adhesive and a second adhesive; The first adhesive includes at least one of polyacrylate, polyacrylic acid, polyacrylamide, and silicon phosphorus sol; The second adhesive includes at least one of polyacrylate, sodium carboxymethyl cellulose, polyacrylic acid, polyacrylonitrile, polyacrylic acid copolymer, and silicon phosphorus sol.
7. The battery separator according to claim 6, characterized in that The mass proportion of the first adhesive in the coating is 1% to 10%; And / or, the mass proportion of the second adhesive in the coating is 0.01% to 2%.
8. The battery separator according to claim 1, characterized in that Satisfy at least one of the following conditions (1) to (5): (1) The average height of the protrusion structure is 2.8 to 30 μm; (2) There are gaps between the inorganic particles, and at least part of the polymer particles are embedded in the gaps; (3) The polymer particles are solid particles; (4) The inorganic particles include at least one of alumina, boehmite, silicon dioxide, magnesium hydroxide, and barium sulfate; (5) The air permeability of the battery separator is 160 to 400 s / 100 cc.
9. A secondary battery, characterized in that: It comprises a positive electrode sheet, a negative electrode sheet and a battery separator according to any one of claims 1 to 8; the average gap between the battery separator and the positive electrode sheet and the negative electrode sheet is 0 to 9 μm.
10. An electrical device, characterized in that: It includes the secondary battery as described in claim 9, and the secondary battery serves as a power supply for the electrical device.
Citation Information
Patent Citations
Composite membrane and electrochemical device
CN114361717A
Battery diaphragm and battery
CN115275524A
Isolating membrane, secondary battery comprising same, and related battery module, battery pack and device
CN118117259A
Heat resistance microporous film, separator for lithium ion secondary batteries, and lithium ion secondary battery
JP2015181110A
Spray separator for lithium ion battery and preparation method therefor
WO2021174709A1
Cited By
Battery
CN120600933A
A battery
CN120600933B
Battery diaphragm, preparation method thereof and secondary battery
CN120674741A
Battery separator, secondary battery and electrical device
WO2026066481A1
Separator and secondary battery
WO2026143990A1
